Proteome analysis of hairy root from Panax ginseng C. A. Meyer using peptide fingerprinting, internal sequencing and expressed sequence tag data - Kim, S.I.; Jin Young Kim; Eun A. Kim; Kyung-Hoon Kwon; Kyung-Wook Kim; Kun Cho; Jeong Hwa Lee; Jeong Hwa Lee; Deok-Chun Yang; Jong Shin Yoo; Young Mok Park
As an initial step to the comprehensive proteomic analysis of Panax ginseng C. A. Meyer, protein mixtures extracted from the cultured hairy root of Panax ginseng were separated by two-dimensional polyacrylamide gel electrophoresis (2-DE). The protein spots were analyzed and identified by peptide finger printing and internal amino acid sequencing by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS)and electrospray ionization quadrupole-time of flight mass spectrometry (ESI Q-TOF MS), respectively. More than 300 protein spots were detected on silver stained two-dimensional (2-D)gels using pH 3-10, 4-7, and 4.5- 5.5 gradients. Major protein spots (159)were analyzed by peptide fingerprinting or de novo sequencing and the functions of 91 of these proteins were identified. Protein identification was achieved using the expressed sequence tag (EST)database from Panax ginseng and the protein database of plants like Arabidopsis thaliana and Oryza sativa. However, peptide mass fingerprinting by MALDI-TOF MS alone was insufficient for protein identification because of the lack of a genome database for Panax ginseng. Only 17 of the 159 protein spots were verified by peptide mass fingerprinting using MALDI-TOF MS whereas 87 out of 102 protein spots, which included 13 of the 17 proteins identified by MALDI-TOF MS, were identified by internal amino acid sequencing using tandem mass spectrometry analysis by ESI Q-TOF MS. W ten the internal amino acid sequences were used as identification markers, the identification rate exceeded 85.3
Keywords: EXPRESSED SEQUENCE TAG DATA; HAIRY ROOT; INTERNAL SEQUENCING; PANAX GINSENG; C. A. MEYER; PEPTIDE FINGERPRINTING; PROTEOME ANALYSIS